Exploring Music Integration for Motivating EFL Students in English Language Learning - Rahmalisa, Fifta; Solusia, Carbiriena (Universitas Negeri Padang, 2025)
This classroom action research investigates the impact of music integration on the motivation of 34 tenth-grade students studying English as a Foreign Language (EFL) at SMAN 1 Solok Selatan in learning recount texts, by answering two research questions: Does music integration have an impact on student motivation, and how does this impact occur? Conducted over three cycles, this study used songs such as “Fifteen” by Taylor Swift, “The Climb” by Miley Cyrus, and “Perfect” by Ed Sheeran to teach the structure of recount texts through activities such as lyric analysis, group collaboration, scaffolding, and role-playing. Pre-test and post-test questionnaires, adapted from AMTB Gardner, measured motivation levels, while an observation checklist assessed engagement using the ARCS model (Attention, Relevance, Confidence, Satisfaction). Research results indicate that integrating music significantly enhances motivation, with average scores increasing from an average of 2.77 on the pre-test to 3.48 on the post-test, an increase of 14.46%. Observational data showed an increase in engagement from 56.94% in Cycle 1 to 85% in Cycle 3. Music enhances motivation by reducing affective barriers, fostering intrinsic engagement through enjoyable tasks, and promoting collaborative learning. Repeated improvements addressed challenges such as low verbal participation, increasing self-confidence (75% in Cycle 3) and satisfaction (100% in Cycles 2 and 3). This study highlights music as an accessible and low-cost tool to transform passive EFL classrooms in rural settings with limited resources into dynamic, student-centered learning environments, offering practical insights for educators in similar contexts.